Adaptive Differential Evolution Algorithm for Single and Multi-Objective Numerical Optimization - Alaraj, Abdallah Ahmad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
“DE/current-to-pbest” is a new and increasingly common mutation strategy that involves an additional external archive and adaptively updates the control. This thesis introduces a novel algorithm known as JADE. The “DE/current-to-pbest” is a simplification of the typical “DE/current-to-best,” while historical data is used by the additional archive operation to provide information on progress direction. Both convergence performance and the diversity of the population are enhanced by the two operations. The control parameters are automatically updated to the appropriate values through parameter adaptation, which avoids relying on outdated information regarding the relationship between the characteristics of the optimization problems and the parameter settings. This thesis work introduces a JADE Algorithm and examines its feasibility based on the results of CEC'17 expensive benchmark problems for single objective optimization problems and for Multi-objective optimization. The methods used in our studies are compared to different well-knows methods proposed in the related literature was conducted. The final ranking of all test problems indicate that JADE was always among the top best algorithms that were used for the same purpose.

ÖZ: “DE/current-to-pbest”, harici ek bir arşiv ile kontrolü adaptif olarak güncelleyen yeni ve giderek daha da yaygın olarak kullanılan bir mutasyon stratejisidir. “DE/current-to-pbest”, özgün olan “DE/current-to-pbest” algoritmasının sadeleştirilmiş halidir. Historik veri, ilerleme yönü hakkında bilgi sağlamak amacı ile ek arşivleme işlemi tarafından kullanılır. Popülasyonun çeşitliliği ve yakınsama performansı, iki operasyon tarafından artırılmıştır. Kontrol parametreleri, optimizasyon problemlerinin karakteristikleri ve parametre ayarları arasındaki ilişki ile ilgili eski bilgilere dayanmaktan kaçınan parametre adaptasyonu ile otomatik olarak uygun değerlere güncellenmektedir. Bu tez çalışması, JADE algoritmasını sunar ve tek amaçlı optimizasyon problemleri ile çok amaçlı optimizasyon için CEC'17 pahalı kriter problemlerinin sonuçlarını baz alarak mümkünlüğünü inceler. Çalışmalarımızda kullanılan yöntemler, literatürde bulunan bilindik yöntemlerle karşılaştırılmıştır. Tüm test problemlerinin son sıralaması JADE’in her zaman aynı amaç için kullanılan en iyi algoritmalar arasında olduğunu göstermektedir.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2019. Supervisor: Assoc. Prof. Dr. Adnan Acan.
Keywords: Computer Engineering; Artificial Intelligence; Artificial Bee Colony; Multi-agent systems; Meta-heuristic algorithms; Multi-objective optimization; evolutionary optimization; Adaptive parameter control; Pareto optimality; differential evolution